The Study of Stroke Knowledge and The Needs of Health Education Pattern Regarding Stroke among People at High – Risk in The 4th Health Region, Thailand - Pongtapthai, Pragasit; Kummabutr, Jeeraporn; Rutchanagul, Pregamol (Journal of The Royal Thai Army Nurses, 2024)
This descriptive research aimed to study stroke knowledge and the need for health education pattern regarding stroke among the high – risk people in the 4th health region. A multistage random sampling of 381 subjects was used to collect data using a questionnaire. Analyzed by descriptive statistics, frequency, percentage, mean, standard deviation, and median The results showed that the samples had a low levelof stroke knowledge ( = 18.55, SD = 7.338) included knowledge of causes, risk factors, signs and warning signs, and stroke management. In addition, the health care providers were needed to be the most senders to inform stroke knowledge ( = 7.53, SD = 2.00) and they needed the big font or visible media ( = 4.46, SD = .851), easily understandable and concise media ( = 4.48, SD = .745). The characteristic of sender is good personality, trustworthiness, and knowledge of stroke ( = 4.4, SD = .757). Therefore, healthcare provider should be adjusting their methods of communicating stroke knowledge and adjust the media for the needs of the people.